Chondroid Lipoma Mimicking Malignancy. Issue 1 (5th May 2022) - Mertens, Kris; Van Beeck, Annelies; Vanhoenacker, Filip
Teaching Point: A chondroid lipoma is a rare benign adipocytic neoplasm, containing a chondromyxoid matrix, that may mimic a myxoid liposarcoma and myxoid chondrosarcoma.